1968
DOI: 10.1901/jeab.1968.11-1
|View full text |Cite
|
Sign up to set email alerts
|

AUTO‐SHAPING OF THE PIGEON'S KEY‐PECK1

Abstract: Reliable acquistion of the pigeon's key‐peck response resulted from repeated unconditional (response‐independent) presentations of food after the response key was illuminated momentarily. Comparison groups showed that acquisition was dependent upon light—food pairings, in that order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
780
5
12

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,539 publications
(812 citation statements)
references
References 14 publications
15
780
5
12
Order By: Relevance
“…Baum (1993) concluded that pausing was a respondent process controlled mainly by the reinforcement rate. These results may be related to research showing the development of schedule-induced interim behavior on responseindependent schedules of reinforcement (e.g., Brown & Jenkins, 1968;Staddon & Simmelhag, 1971;see Staddon, 1977, for a review).…”
Section: Discussionmentioning
confidence: 67%
“…Baum (1993) concluded that pausing was a respondent process controlled mainly by the reinforcement rate. These results may be related to research showing the development of schedule-induced interim behavior on responseindependent schedules of reinforcement (e.g., Brown & Jenkins, 1968;Staddon & Simmelhag, 1971;see Staddon, 1977, for a review).…”
Section: Discussionmentioning
confidence: 67%
“…Crucial to the understanding of sign-tracking, the US is delivered regardless of what the subject does. Repeated CS-US pairings lead to the acquisition of the Pavlovian sign-tracking CR, which is a complex sequence of motor responses directed at the CS (Brown and Jenkins, 1968; for review, see Tomie et al, *Corresponding Author. Department of Psychology, Rutgers University, New Brunswick, NJ USA 08903.…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals with a propensity to form and respond to Pavlovian stimulus-reward associations have been suggested to be more vulnerable to addictive drugs (Tomie, 1996). It is therefore important to understand the neural mechanisms by which animals learn associations between stimuli and rewards, and the manner in which such associations control behavior.Autoshaping (Brown & Jenkins, 1968) is a measure of Pavlovian stimulus-reward learning in which subjects approach a CS that predicts reward. In a typical autoshaping task designed for use with rats , a visual stimulus (CSϩ) is presented on a computer screen and followed by delivery of food at a different location.…”
mentioning
confidence: 99%